Integrating Culture and Environmental Education for Sustainability to Develop Values - Ghildyal, Prachi; Dey, Tulika (JOURNAL OF INDIAN EDUCATION, 2020)
India is a traditional country with values ingrained in its culture. The values absorbed in the early years of life are long lasting in life and therefore values are gradually taking their rightful place in the education system. Value-based environmental education can bring in a total transformation of our mindset, attitudes and lifestyles. The objective of this paper is to identify few cultural practices ingrained in the Indian cultural heritage, and bring out a few strategies to expose children to the strong value system, to achieve sustainability by caring for the nature.